2018
DOI: 10.1111/irel.12214
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Ask?

Abstract: Females typically earn less than males. The reasons are not fully understood. This paper re‐examines the idea that women “don't ask,” which potentially assigns part of the responsibility for the gender pay gap onto female behavior. Such an account cannot readily be tested with standard datasets. This paper is the first to be able to use matched employer–employee data in which workers are questioned about their asking behavior. It concludes that males and females ask equally often for promotions and raises. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 47 publications
2
106
0
Order By: Relevance
“…However, there is a clear pattern in tenure with the employer, where individuals with tenure of less than one year are most likely to report having the opportunity to negotiate over pay. Artz, Goodall, and Oswald () found a similar relationship between job tenure and whether Australian workers’ wages are negotiable. There is some evidence that the opportunity to negotiate is inversely related to the individual's level of education, though jobs which require higher levels of skill are associated with a significantly greater propensity on the part of the respondent to report having the opportunity to negotiate.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…However, there is a clear pattern in tenure with the employer, where individuals with tenure of less than one year are most likely to report having the opportunity to negotiate over pay. Artz, Goodall, and Oswald () found a similar relationship between job tenure and whether Australian workers’ wages are negotiable. There is some evidence that the opportunity to negotiate is inversely related to the individual's level of education, though jobs which require higher levels of skill are associated with a significantly greater propensity on the part of the respondent to report having the opportunity to negotiate.…”
Section: Resultsmentioning
confidence: 79%
“…In comparison, part‐time workers and those employed in the public sector are substantially less likely to report having the opportunity to negotiate over pay. Artz, Goodall, and Oswald () also found that wages are increasingly likely to be negotiable as the number of hours worked rises.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations